‘CURA AQUARUM’ W PRAWIE RZYMSKIM - Renata Kamińska (Zeszyty Prawnicze)
‘CURA AQUARUM’ IN ROMAN LAW Summary The supervision over public waters was one of the most important tasks of Roman administration. In the republic the control and protection of public waters belonged to censors and aediles since there was no separate offices relevant exclusively in this extent. Firstly, censors were responsible for maintaining the proper water status in the Tiber as well as the prevention and removal of the devastation caused by periodic flooding. Secondly, were their tasks related to supply water to the City of Rome. They took care to ensure both continuity of water supplies, as well as they were also required to maintain the state aqueducts. In turn, aediles exercised the control over the central distribution and water quality.  The proper cura aquarum developed in the principate together with the establishment of the office curatores aquarum. They were appointed on the initiative of Octavian Augustus in 11 BC on the basis of the senatus consultum de aquaeductibus. This office gradually strengthened. This was reflected in the gradual takeover by curatores functions so far carried out by aediles and censors. In 11 (15) BC a new office of curatores riparum et alvei Tiberis was established, which in the year 101 the Emperor Hadrian transformed into curatores riparum et alvei Tiberis et cloacarum Urbis. Curatores riparum occupied the highest position in the hierarchy of cura aquarum.